(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This descriptive cross-sectional study was carried out toassess the nutritional status of children aged 4-5year children, Muzaffarnagardistrict, Uttar Pradesh, in order to establish and provide baseline informationon the health and nutritional status of the target group. Nutritional statuswas assessed using anthropometric measurements of height, weight and wascompared with NCHS standards. The nutrient intakes were compared with theRecommended Dietary Allowance (RDA).The intakes of protein, iron, calcium andvitamin A were inadequate in both males and females children. The findings showthat the nutritional status of Under-5 children in the study location whichhappens to be a rural area was quite poor. Also from the results, it is evidentthat malnutrition is still a major public health problem. There is a need forbetter nutrition of child.